Social Dynamics of Collaborative Management in Coastal Conservation: Community Participation in Negeri Lima, Central Maluku - Fathir Muhlis Soulisa; Josep Antonius Ufi; Maryam Salampessy (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the Study: This study aims to analyze collaborative management in coastal conservation programs in Negeri Lima, Leihitu Subdistrict, Central Maluku Regency, by examining how planning, organizing, commanding, coordinating, and controlling functions are practiced through multi-stakeholder participation. Methodology: This study employed a qualitative descriptive design. Data were collected through observation, semi-structured interviews, documentation review, and literature study. Fifteen informants were selected purposively from Harmoni Alam Indonesia, village government, marine and fisheries authorities, environmental organizations, and community members. Data were analyzed through reduction, display, thematic interpretation, and verification. Main Findings: The findings show that collaborative management strengthened stakeholder interaction, shared responsibility, and community involvement in coastal conservation. Planning and organizing created clearer program direction, while commanding and coordinating encouraged collective action. However, unequal participation, limited technical capacity, weak communication mechanisms, and non-standardized monitoring reduced the depth of collaboration. These conditions reveal that conservation is not only ecological work but also a social process involving power relations, trust, local knowledge, and institutional learning. Novelty/Originality of this Study: This study contributes by applying Henri Fayol's classical management functions to analyze collaborative coastal conservation in a small-island village context. It offers a socio-managerial perspective that links stakeholder participation, community agency, and coastal governance, thereby enriching studies on collaborative management in coastal societies.